1995
DOI: 10.1002/ace.36719956606
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring program practices and effectiveness

Abstract: A study of fifteen mentoring programs and a close examination of the Sponsor‐A‐Scholar program offer insights into the design and effectiveness of mentoring programs for at‐risk young adults, the components of a model program, and comprehensive program evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…One possible answer is that participation in these mentoring programmes did not result in the anticipated positive outcomes. From the research we know that the positive effects of mentoring on the criterion 'school success' are very difficult to demonstrate (Johnson & Sullivan, 1995). Jacobi (1991), basing his findings on a literature survey, observed that it is unclear whether mentoring contributes to educational success, and if there is a relationship between participation in a mentoring programme and school success, it is unclear how this relationship comes about.…”
Section: Introductionmentioning
confidence: 94%
“…One possible answer is that participation in these mentoring programmes did not result in the anticipated positive outcomes. From the research we know that the positive effects of mentoring on the criterion 'school success' are very difficult to demonstrate (Johnson & Sullivan, 1995). Jacobi (1991), basing his findings on a literature survey, observed that it is unclear whether mentoring contributes to educational success, and if there is a relationship between participation in a mentoring programme and school success, it is unclear how this relationship comes about.…”
Section: Introductionmentioning
confidence: 94%
“…Although converse outcomes have also been identified (e.g., Johnson & Sullivan, 1995; Keating, Tomishima, & Foster, 2002; Roberts, Liabo, Lucas, DuBois, & Sheldon, 2004), positive interpersonal relationships with extrafamilial adults have received growing attention and empirical support in recent years as a protective influence in the lives of youth, especially in the United States (cf. Grossman & Rhodes, 2002; Herrera, Sipe, & McClanahan, 2000).…”
mentioning
confidence: 99%
“…An extensive orientation programme emphasizing the development of realistic expectations, stating responsibilities for the mentor, establishing criteria for duration and frequency of contacts, and training of mentoring skills should be conducted for mentors. Johnson and Sullivan (1995) alluded that training is vital if a mentoring programme is to be successful, as the mentoring role does not come naturally. 4.…”
Section: Resultsmentioning
confidence: 98%
“…Literature reveals that training is important if the programme is to be successful; some type of training is vital as the mentoring role does not come naturally (Johnson & Sullivan, 1995;Stott & Walker, 1992). The training given to mentors is to familiarize them with both the overall goals of the mentoring programme and the techniques of mentoring (Zey, 1993).…”
Section: Mentoring In Educationmentioning
confidence: 98%